(untitled) (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the theoretical substantiation of role of emotional flimness as a necessary index of future teacher’s professional experience. The essence of the term and peculiarities of its displaying in the context of professional activity of teacher as his stability factor are revealed.